Medical Students’ Knowledge and Perceptions of Herbal Medicine in Saudi Arabia: Should Medical Schools Take Immediate Action? - Almech M; Alissa A; Baghdadi RA; Abujamai JZ; Hafiz W; Alwafi H; Shaikhomer M; Alshanberi AM; Alshareef MH; Alsanosi SM (Advances in Medical Education and Practice)
Majd Almech,1 Abdulrahim Alissa,1 Ragad Adel Baghdadi,2 Jakleen Z Abujamai,1 Waleed Hafiz,3 Hassan Alwafi,4 Mohammed Shaikhomer,5 Asim M Alshanberi,1,6 Maram H Alshareef,6 Safaa M Alsanosi4 1General Medicine Program, Batterjee Medical College, Jeddah, 21442, Saudi Arabia; 2Faculty of Medicine, Umm Al-Qura University, Makkah, Saudi Arabia; 3Department of Medicine, Faculty of Medicine, Umm Al-Qura University, Makkah, Saudi Arabia; 4Department of Pharmacology and Toxicology, Faculty of Medicine, Umm Al Qura University, Makkah, Saudi Arabia; 5Department of Internal Medicine, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 6Department of Community Medicine and Pilgrims Health Care, Faculty of Medicine, Umm Al Qura University, Makkah, Saudi ArabiaCorrespondence: Safaa M Alsanosi, Email smsanosi@uqu.edu.saBackground: Herbal medicine is integral to Saudi Arabia’s Vision 2030, which seeks to improve the healthcare system and promote alternative practices while ensuring safety through education and research. This study aims to evaluate medical students’ knowledge and perceptions regarding herbal medicine in Saudi Arabia.Methods: A cross-sectional study was conducted among medical students in three medical colleges in Saudi Arabia over a six-month period from 1 February to 31 July 2024. Descriptive statistics were used to describe the participants’ characteristics, and categorical variables were reported as frequencies and percentages. A chi-square test was used to test the relationships between variables. A p-value of < 0.05 was taken to indicate statistical significance.Results: In total, 592 participants were included in the study. Females represented 65.7% of the participants. While 72.6% of the students agreed that medical students lack proper knowledge about the use of herbal medicines, 64.9% preferred having an elective course in complementary medicine (including herbal medicine). Also, 40.9% of students use herbal medicine believing they do not require expert knowledge and can safely experiment with various herbs, and 22.3% use it because they perceive it as having no side effects due to its natural ingredients. The most reported sources of information included family and friends (53.2%), whereas traditional herbalists (Attar) were the most reported sources of herbs (49.3%). The most used herbs among medical students were ginger (83%), turmeric (48.1%), chamomile (46.3%), and myrrh (26.5%). Only 37.7% of students who used herbs had an overall good knowledge and perception of them (P = 0.001). Gender showed a significant relationship with herb use among the students: 95.4% of female students used herbs, compared with 92.6% of male students (P = 0.049).Conclusion: A considerable proportion of medical students demonstrated insufficient knowledge and perception regarding the use of herbal medicine. To improve their understanding, it is essential to integrate comprehensive courses, organize workshops led by experts, promote research and clinical experiences, and establish patient education initiatives.Keywords: medical students’, herbal medicine, Saudi Arabia, medical schools